Isogambogenic acid inhibits tumour angiogenesis by suppressing Rho GTPases and vascular endothelial growth factor receptor 2 signalling pathway. (1st October 2013) - Fan, Yi; Peng, Aihua; He, Shichao; Shao, Ximing; Nie, Chunlai; Chen, Lijuan
<x xml:space="preserve">Abstract</x> Isogambogenic acid (iso-GNA) is a well-known herbal medicine extracted from Garcinia hanburyi. Although it is thought to have anti-tumour effects, its function is still unknown. This study carried out in vitro and in vivo evaluations of the anti-tumour and anti-angiogenic activity of iso-GNA and underlying mechanisms. A standard methyl thiazolyl tetrazolium assay showed that iso-GNA was more effective in inhibiting the proliferation of human umbilical vascular endothelial cells than A549 cancer cells. Iso-GNA demonstrated potent anti-angiogenic activity and low toxicity at appropriate concentrations in zebrafish embryos. In a xenograft nude mouse model of lung tumour, iso-GNA effectively inhibited tumour growth and tumour angiogenesis. Iso-GNA suppressed neovascularization of implanted matrigel plugs in vivo and inhibited vascular endothelial growth factor (VEGF)-induced microvessel sprouting from mouse aortic rings ex vivo. Iso-GNA inhibited VEGF-induced migration, invasion, and tube formation in vitro and affected cytoskeletal rearrangement in human umbilical vascular endothelial cells. The results show that iso-GNA suppressed angiogenesis-mediated tumour growth by targeting VEGFR2, Akt, mitogen-activated protein kinase, Rho GTPase, vascular endothelium-cadherin, and focal adhesion kinase signalling pathways. Together, these data suggest that iso-GNA inhibits angiogenesis and may be a viable drug candidate in anti-angiogenesis and anti-cancer therapies.